Kinetic Analysis of Solar-Dried Mango (Mangifera Indica L.) Slices Via Thin-Layer Models - Elmsaad, Egbal; Elmahi, Omer; Omran, Abdelnaser; Emam, Abda (Journal of Environmental Management and Tourism, 2026)
Drying is an important technology for preserving crops and reducing post-harvest losses. Solar dryers play a significant role in drying some vegetable and fruit crops. They are economical, technically cost-effective, and energy-saving, as they rely on sunlight for drying. This study aimed to investigate the drying kinetics of thin mango slices in a multi-mode solar dryer. The experiment was conducted on three slice thicknesses (4, 6, and 8 mm) during drying. The results showed that several thin-layer drying models were fitted to the experimental data. Based on the highest R² (coefficient of determination) values and the lowest χ² (chi-square) and RMSE (root mean square error) values, the Page model was determined to be the most appropriate for describing the drying kinetics, with R² value was 0.9971. The effective moisture diffusion coefficient (Deff) was calculated using Fick's second law and ranged from 3.31 × 10⁻¹⁰ to 9.77 × 10⁻¹⁰ m²/s, increasing with increasing air velocity and decreasing slice thickness. A simulation model based on Page’s equation and empirical relationships for (Deff) was measured and successfully validated against experimental data, proving it to be an effective tool for predicting drying behavior and optimizing solar drying processes for mango slices.